Low grade heat driven multi-effect distillation and desalination - Chua, Hui Tong; Rahimi, Bijan (Elsevier, 2017)
Low Grade Heat Driven Multi-effect Distillation and Desalination describes the development of advanced multi-effect evaporation technologies that are driven by low grade sensible heat, including process waste heat in refineries, heat rejection from diesel generators or microturbines, and solar and geothermal energy. The technologies discussed can be applied to desalination in remote areas, purifying produced water in oil-and-gas industries, and to re-concentrate process liquor in refineries. This book is ideal for researchers, engineering scientists, graduate students, and industrial practitioners working in the desalination, petrochemical, and mineral refining sectors, helping them further understand the technologies and opportunities that relate to their respective industries. For researchers and graduate students, the core enabling ideas in the book will provide insights and open up new horizons in thermal engineering.